Anatomical alterations of the main bile duct of mechanical etiology as findings during intraoperative cholangiography - Perdomo, Mauro; Bentancur, Martín; Valsangiacomo, Pablo; González, Daniel (Cirugía del Uruguay, 2021)
Two intraoperative cholangiographies performed in the context of coordinated laparoscopic cholecystectomies are presented.